Implementasi Fatwa DSN MUI Terhadap Pembiayaan Sindikasi Melalui Akad Musyarakah Pada BPRS HIK Cibitung - Santiya, Ayu; Fahlevi, Rizal (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
The Syndicated financing is one of the strategies that can be carried out by Islamic banking, especially Islamic people's financing banks to get a relatively safe boost of Islamic banking industry assets. With the implementation of syndication, Islamic banking can enter the corporate sector and government infrastructure projects. BPRS has the potential to earn large profits, but can also mitigate relatively large risks.This study aims to find out how the implementation of syndicated musharaka financing at BPRS HIK Cibitung and analysis of syndication financing conformity with the DSN fatwa Number 91/DSN-MUI/IV/2014.This research is a qualitative research. Sources of data in the form of primary data, and secondary data. Primary data was obtained by conducting interviews with the BPRS HIK Cibitung. Literature studies were obtained from books, journals, official websites and documents related to syndicated financing. The data analysis technique was carried out in three steps, namely data reduction, data presentation, and drawing conclusion. The results of this study indicate that the syndicated financing at BPRS HIK Cibitung is in accordance with the fatwa dsn-mui number 91 of 2014. However, there are several points in the fatwa dsn-mui that have never been used by BPRS HIK Cibitung.